2008
DOI: 10.1186/1471-2172-9-32
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo recovery and activation of dysfunctional, anergic, monocyte-derived dendritic cells from patients with operable breast cancer: critical role of IFN-alpha

Abstract: Background: Dendritic cells (DCs) play a crucial role in initiating effective cell-mediated immune responses, but are dysfunctional and anergic in breast cancer. Reversal of this dysfunction and establishment of optimal DC function is a key prerequisite for the induction of effective anti-cancer immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…26 It has been suggested that rhIFNα 2 b plays important roles in antitumor and antiviral activity and regulation of the immune system. 3,[8][9][10][11][12][13][14][15][16] The mechanism of the antitumor effect is not completely clear yet. However, studies have suggested it might inhibit tumor growth in vivo through tumor cellgrowth inhibition, tumor-cell apoptosis, oncogene-expression restraint, immune-system regulation, and tumor-angiogenesis suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 It has been suggested that rhIFNα 2 b plays important roles in antitumor and antiviral activity and regulation of the immune system. 3,[8][9][10][11][12][13][14][15][16] The mechanism of the antitumor effect is not completely clear yet. However, studies have suggested it might inhibit tumor growth in vivo through tumor cellgrowth inhibition, tumor-cell apoptosis, oncogene-expression restraint, immune-system regulation, and tumor-angiogenesis suppression.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Some studies show that IFNα, including IFNα 2 b, is also capable of exerting antitumor effects against HCC, hairy cell leukemia, lymphoma, melanoma, and breast cancer. 3,[8][9][10][11][12][13][14][15][16] However, an extensive clinical trial of IFNα 2 b for HCC was delayed, due to the weak therapeutic effect based on conventional drug-delivery methods. In general, these methods cause rapid degradation of IFNα 2 b in the body and induce severe side effects, due to the systemic distribution of drugs in the body causing bone marrow suppressions and neurologic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…CD86 is constitutively expressed on antigenpresenting cells (APC), whereas CD80 expression is induced upon APC activation. Cancers, including breast cancers (12)(13)(14)(15), show an abundance of immature DCs with impaired capacity to stimulate antitumor immunity (16). In cancer, the main mechanisms of immune evasion resulting in impaired antitumor T-cell response are (i) the lack of expression of costimulatory ligands such as CD80 and CD86 on APCs (8) and (ii) the increased number of T regulatory cells (Treg; ref.…”
Section: Introductionmentioning
confidence: 99%
“…This was the rationale for choosing to compare TNF-α by itself or in combination with IFN-α as a maturation and activation factor for ex vivo monocyte-derived DCs, instead of the standard Jonuleit's DC maturation cocktail. Our previous work in vitro had demonstrated that monocyte-derived DCs matured with TNF-α and IFN-α were phenotypically and functionally superior to DCs matured with TNF-α alone[ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…We compared hTERT-specific CD8+T cell responses elicited in vivo between the above two DC preparations. In our previously published work we had shown that this cytokine combination (GM-CSF, IL-4, TNF-α ± IFN-α) was capable of generating DCs in vitro from CD14+ monocytes obtained from healthy individuals and patients with cancer[ 36 ]. These DCs were activated but relatively immature, strongly phagocytic and induced CD8+T cell responses in vitro .…”
Section: Introductionmentioning
confidence: 99%